The influence of viewing context on meaning making : a reception study of the popular drama series Intersexions in Ginsberg township - Ponono, Mvuzo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
This study examines the home as a context of viewing for the television programme Intersexions in the township of Ginsberg in the Eastern Cape. The central question asked is whether the household influences the interpretation of the programme. The research was mainly conducted through ethnographical methods of participant observation and focus group interviews. Six families were observed and six gender-based focus groups convened. Drawing from the work of Morley (1986) and Lull (1990) that argues that the home be taken more seriously as a context of viewing; this study posits that the home is a rule-bound micro-society that influences the interpretation of media messages. As a starting point, this study contends with the arguments that the South African government has been slow to acknowledge the extent of the problem presented by the HIV/AIDS pandemic. Much has been written about the inefficiency of state efforts to educate the public, with some pundits suggesting that government communications strategies have largely been outdated and thus resisted by audiences (Treffry-Goatley, Mahlinza & Imrie, 2013). To counter the pandemic, a large number of independent educational television serials have been launched in South Africa, and met with popular appeal since 1994. Furthermore, this development is in line with global trends of high audience ratings for Entertainment- Education (EE) programmes (Singhal et al., 1993). To investigate complex issue of EE reception by audiences in this burgeoning area of study, the programme at the centre of this study, Intersexions, is a good example. The serial, which concluded its second season in August 2013, is second to only the established soap opera, Generations, in television ratings in South Africa. Therefore, the impressive ratings garnered by educational serials in South Africa are a chance for audience studies to study audiences in context. This research investigates Intersexions using the understanding that television audiences must be analysed in "cultural and historic specific" sites because the struggle to make meanings of texts takes place at the moment when the text and subject meet (Fiske, 1987). This research investigates the assumption that the meanings made by audiences depend not just on the text, but also on environment. This means that the research delves into the situational context in which media are used and interpreted. Therefore, the central aim of this study is to analyse television viewing of the entertainment education programme, Intersexions, in the natural setting of the home, which is in line with analysing television viewers in cultural and historically specific sites.
Keywords: Intersexions (Television program); Meaning (Psychology); Context effects (Psychology); Television programs -- South Africa; Television -- Social aspects -- South Africa; Television viewers -- South Africa -- Eastern Cape; Television viewers -- South Africa -- Eastern Cape -- Attitudes; Educational television programs -- South Africa; AIDS (Disease) in mass media -- South Africa; South Africa -- Social life and customs